Mortality of Monarch Butterflies (Danaus plexippus) at Two Highway Crossing “Hotspots” During Autumn Migration in Northeast Mexico - Mora Alvarez, Blanca Xiomara; Carrera-Treviño, Rogelio; Hobson, Keith A. (Frontiers in Ecology and Evolution, 2019)
The contribution to annual mortality of migrating monarch butterflies (Danaus plexippus) due to collisions with vehicles is poorly understood but likely significant. Recent estimates based on a study in Texas suggests that mortality during autumn migration may be of the order of 2 million per year or about 3% of the population. However, MaxEnt models used in that study are not well suited to quantifying mortality at hotspots where monarchs are concentrated by topography such as canyons when crossing highways. Potentially catastrophic mortality could occur at such sites if timing of migration and weather conditions conspire to force a large proportion of the migrating population across highways at low altitude. We investigated monarch mortality 15 October to 11 November, 2018 at two highway crossings in northeastern Mexico known for their frequent and extensive collisions (La Muralla and Santa Catarina). During a 15-19 day period of migration, we collected dead and injured monarchs along a series of 500 m roadside transects. We estimated a minimum total mortality during fall migration at just these sites of about 196,560 individuals. Monarchs exhibited a diurnal pattern of passage at Santa Catarina of peaks in late morning and late afternoon. Average vehicle speeds exceeded posted 60 km/h limits designed to protect monarchs, ranging from 75.1 to 99.6 km/h at La Muralla and 86.6 to 106.8 km/h at Santa Catarina. We recommend finer-scale documentation of migration pathways and an inventory of significant highway crossing hotspots for monarchs during fall migration in northeast Mexico. Mitigative measures could include better enforced vehicle speeds at least during the short period of migration, deflection structures to raise the height of crossing monarchs and/or manipulation of habitat to lower the potential for monarchs descending to roost near key crossing points.